Model Pembelajaran Multikulturalisme Guru Pendidikan Agama Islam - Abdul Halim (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2022)
Information technology is increasingly developing and has an impact on the fact that the world seems to be borderless, which is a challenge in the world of education, especially Islamic religious education. The term global village as an impact of globalization leads to a model of life in which various cultures meet and interact more intensely ideological contestation, and cross-cultural communication. Therefore this reality must be addressed wisely and prudently. If cultural diversity and differences are not managed properly, it will have an impact on disharmony and polarization in society. One of the efforts to respond to this reality is multiculturalism. Education in Indonesia, especially Islamic education, requires a learning model based on multiculturalism, bearing in mind that Indonesia as a plural country is required to care for and manage its diversity properly. This study took the locus of Mojokerto district where the subject of this study was a PAI teacher. This study uses a qualitative approach to data that will be collected and analyzed and tested for its validity through technical credibility, transferability, confirmability, and dependability. The results of the study illustrate that the multiculturalism learning model for PAI teachers is based on the reality of the elements and structure of PAI learning including multiculturalism and its values. In addressing the cultural diversity of students, teachers practice multicultural values ​​such as tolerance. In the realm of objectives, materials, media, methods, and evaluation of Islamic education teachers are required to internalize it with multiculturalism and its values ​​such as tolerance and mutual respect.